Theory of Ibn ʿArabī in the Cosmic Symptoms - Mohd. Shamsuddin, Salahuddin; Abd Rahman, Mohammad Zaki; Pa, Mat Taib (KATHA- The Official Journal of the Centre for Civilisational Dialogue, 2018)
Ibn ʿArabī believes that the cosmic symptoms or fact of the facts is one of the manifestations of the mediator between the divine and the world. Its mediation means that it represents the contents of old divine knowledge. The science is a fact in the psychology related to the nonexistent and existent. The fact of the facts or the total truth is the sum of the facts that constitute the divine science. The science belongs to both: The nonexistent and existent. Ibn ʿArabī is in the favor of idealistic philosophy of Plato: “Everything has created on the image of its essence, the essences of things are prior to their existence”, i.e., it was in the divine knowledge when it was in the nothingness. Thus Ibn ʿArabī avoids the presence of any existent had its real existence before being in the divine knowledge. The total fact of the facts cannot be labeled by “the possible”, as it is understood that the total fact of the facts do not accept the real existence, which can be acceptable to the possible, although it is possible for the total fact to appear in the features of real existence as it is in the reality.